Lattice Boltzmann method simulation of ice melting process in the gas diffusion layer of fuel cell. (March 2020) - He, Pu; Chen, Li; Mu, Yu-Tong; Tao, Wen-Quan
Highlights: A pore-scale model combining the LBM and EBM for ice melting is established. The effects of design parameters of GDL on the melting process are investigated. The GDL melting positions have a significant effect on the melting process. The increase of Rayleigh number has a promoting effect on the melting process. The increase of Stefan number can promote the melting process significantly. Abstract: A 2D lattice Boltzmann model combining the enthalpy-based method (EBM) is established to investigate the ice melting process in the gas diffusion layer (GDL). The effects of GDL melting position, porosity, Rayleigh number and Stefan number on the melting rate, ending time of melting, temperature distribution and solid-liquid interface distribution are investigated. It is found that the GDL melting positions have a significant effect on the melting process, the melting rate in the In-plane position increases fastest. When the porosity is large, the effect of the carbon fiber layer number on the melting process is more significant than that of the carbon fiber length. In the In-plane position, the increase of natural convection intensity has a promoting effect on the ice melting process. The increasing of Stefan number can promote the melting process significantly when the Stefan number is not high. And reducing the GDL porosity can effectively promote the melting process.